Hoiamide A, a Sodium Channel Activator of Unusual Architecture from a Consortium of Two Papua New Guinea Cyanobacteria - Pereira, Alban (2009)
Hoiamide A, a novel bioactive cyclic depsipeptide, was isolated from an environmental assemblage of the marine cyanobacteria Lyngbya majuscula and Phormidium gracile collected in Papua New Guinea. This stereochemically complex metabolite possesses a highly unusual structure which likely derives from a mixed peptide-polyketide biogenetic origin, and includes a peptidic section featuring an acetate extended and S-adenosyl methionine modified isoleucine moiety, a triheterocyclic fragment bearing two a-methylated thiazolines and one thiazole, as well as a highly oxygenated and methylated C15-polyketide substructure. Pure hoiamide A potently inhibited [(3)H]batrachotoxin binding to voltage-gated sodium channels (IC(50) = 92.8 nM) and activated sodium influx (EC(50) = 1.73 μM) in mouse neocortical neurons, as well as exhibited modest cytotoxicity to cancer cells. Further investigation revealed that hoiamide A is a partial agonist of site 2 on the voltage gated sodium channel.